2019
DOI: 10.1021/jacs.9b05807
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Thin Metal Sulfides

Abstract: We developed a method to colloidally synthesize atomically thin metal sulfides (ATMS). Unlike conventional 2D systems such as MoS2 and graphene, none of the systems developed here are inherently layered compounds nor have known layered polymorphs in their bulk forms. The synthesis proceeds via a cation-exchange reaction starting from single- and multi-layer Ag2S and going to various metal sulfides. The synthesized ATMS retain their size and shape during the cation-exchange reaction and are either single-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Importantly, we did not observe any signs of Ag 2 S diffraction signals, yet the material displayed the typical absorption and emission features often attributed to Ag 2 S quantum confined nanocrystals. 6,[12][13][14][15] This indicates that the characteristic optical properties (absorbance peak at B800 nm) of materials produced by the reaction of AgNO 3 and MPA in EG stem from Ag-MPA coordination polymer and not from Ag 2 S nanocrystals. Interestingly, TEM and AFM analyses revealed that the web-like structure is even more pronounced than for aliquot II, the orange Ag-MPA(UV) (see Fig.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Importantly, we did not observe any signs of Ag 2 S diffraction signals, yet the material displayed the typical absorption and emission features often attributed to Ag 2 S quantum confined nanocrystals. 6,[12][13][14][15] This indicates that the characteristic optical properties (absorbance peak at B800 nm) of materials produced by the reaction of AgNO 3 and MPA in EG stem from Ag-MPA coordination polymer and not from Ag 2 S nanocrystals. Interestingly, TEM and AFM analyses revealed that the web-like structure is even more pronounced than for aliquot II, the orange Ag-MPA(UV) (see Fig.…”
mentioning
confidence: 97%
“…5 Ag 2 S QDs with tunable photoluminescence feature, 6 ultra low cytotoxicity 7 and strong emission in the NIR window are promising for biological applications, such as imaging in vivo, 8 drug delivery 9 and biosensors, 10 since they allow for deeper tissue imaging than possible with visible light in addition to lower background photoluminescence and thus lower signal-to-noise ratios. 11 Interestingly, in literature, many Ag 2 S QDs and nanoplatelets were prepared by nearly identical wet-chemical approaches, 6,[12][13][14][15] utilizing AgNO 3 and 3-mercaptopropionic acid (MPA) as precursors and ethylene glycol (EG) as solvent with reaction temperatures between 120-145 1C. According to literature, these protocols yield nanomaterials with a variety of polymorphs, sizes, and shapes while at the same time exhibiting nearly identical optical features such as first absorption peaks at B800 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The distance of ∼37.1 Å is in accordance with a bilayer-framework involving DDT, which possesses a chain-length of 17.7 Å when fully extended. 39 The decreased spacing for increased concentration of EDPA can be attributed to replacing some of the long-chain DDT with EDPA possessing a shorter carbon chain-length resulting in the relatively reduced average distance between layers. The shift of peaks in the low angle XRD pattern of Cu−thiolate toward higher angles with increased EDPA concentration is consistent with the replacement of long-chain DDT with short-chain EDPA.…”
mentioning
confidence: 99%
“…Currently available strategies are mostly based on the wet chemical synthesis (e.g., self-assembly, 16,17 oriented attachment, 18,19 lamellar intermediate-assisted exfoliation [20][21][22] and topochemical transformation [23][24][25][26] ), typically using soft or hard templates to direct the anisotropic growth of the non-layered crystals. [27][28][29][30] However, these methods always require very stringent experimental conditions and can hardly be extended to synthesize other 2D non-layered materials.…”
mentioning
confidence: 99%